Association of genetic variants in complement factor H and factor H-related genes with systemic lupus erythematosus susceptibility. - Jian Zhao; Hui Wu; Melanie Khosravi; Huijuan Cui; Xiaoxia Qian; Jennifer A Kelly; Kenneth M Kaufman; Carl D Langefeld; Adrienne H Williams; Mary E Comeau; Julie T Ziegler; Miranda C Marion; et al. (PLoS Genetics)
Systemic lupus erythematosus (SLE), a complex polygenic autoimmune disease, is associated with increased complement activation. Variants of genes encoding complement regulator factor H (CFH) and five CFH-related proteins (CFHR1-CFHR5) within the chromosome 1q32 locus linked to SLE, have been associated with multiple human diseases and may contribute to dysregulated complement activation predisposing to SLE. We assessed 60 SNPs covering the CFH-CFHRs region for association with SLE in 15,864 case-control subjects derived from four ethnic groups. Significant allelic associations with SLE were detected in European Americans (EA) and African Americans (AA), which could be attributed to an intronic CFH SNP (rs6677604, in intron 11, P(meta) = 6.6×10(-8), OR = 1.18) and an intergenic SNP between CFHR1 and CFHR4 (rs16840639, P(meta) = 2.9×10(-7), OR = 1.17) rather than to previously identified disease-associated CFH exonic SNPs, including I62V, Y402H, A474A, and D936E. In addition, allelic association of rs6677604 with SLE was subsequently confirmed in Asians (AS). Haplotype analysis revealed that the underlying causal variant, tagged by rs6677604 and rs16840639, was localized to a ~146 kb block extending from intron 9 of CFH to downstream of CFHR1. Within this block, the deletion of CFHR3 and CFHR1 (CFHR3-1Δ), a likely causal variant measured using multiplex ligation-dependent probe amplification, was tagged by rs6677604 in EA and AS and rs16840639 in AA, respectively. Deduced from genotypic associations of tag SNPs in EA, AA, and AS, homozygous deletion of CFHR3-1Δ (P(meta) = 3.2×10(-7), OR = 1.47) conferred a higher risk of SLE than heterozygous deletion (P(meta) = 3.5×10(-4), OR = 1.14). These results suggested that the CFHR3-1Δ deletion within the SLE-associated block, but not the previously described exonic SNPs of CFH, might contribute to the development of SLE in EA, AA, and AS, providing new insights into the role of complement regulators in the pathogenesis of SLE.